Solar Water Heating as a Potential Source for Inland Norway Energy Mix - Hagos, Dejene Assefa; Gebremedhin, Alemayehu; Zethraeus, Björn (Journal of Renewable Energy, 2014)
The aim of this paper is to assess solar potential and investigate the possibility of using solar water heating for residential application in Inland Norway. Solar potential based on observation and satellite-derived data for four typical populous locations has been assessed and used to estimate energy yield using two types of solar collectors for a technoeconomic performance comparison. Based on the results, solar energy use for water heating is competitive and viable even in low solar potential areas. In this study it was shown that a typical tubular collector in Inland Norway could supply 62% of annual water heating energy demand for a single residential household, while glazed flat plates of the same size were able to supply 48%. For a given energy demand in Inland Norway, tubular collectors are preferred to flat plate collectors for performance and cost reasons. This was shown by break-even capital cost for a series of collector specifications. Deployment of solar water heating in all detached dwellings in Inland could have the potential to save 182 GWh of electrical energy, equivalent to a reduction of 15,690 tonnes of oil energy and 48.6 ktCO2 emissions, and contributes greatly to Norway 67.5% renewable share target by 2020.